Avaliação da viabilidade de métodos de análise da sensibilidade barorreflexa e de um modelo de estudo com a cascavel sul americana (Crotalus durissus) - Rocha, Gabriella Campos (2019)
The autonomic nervous system (ANS) regulate and coordinate processes and function of organs to maintain homeostasis of the cardiovascular system in response of changes in the internal environment. Frequently, the understanding of the response patterns, interaction reflexes and other factors regulated by ANS, required in vivo studies. The use of anesthetics during the course of experimental protocols and data collection has been a way of solving the problems related of such studies. However, anesthetics depress the nervous system and compromise the conclusions from investigations that rely on functional ANS. Thus, in this work, we sought to validate a decerebrated preparation with individuals of the species Crotalus durissus. Decerebration consists in the ablation of superior brain areas in order to maintain preparations that are incapable of superior processing, perception and sensations of any type, including stress or pain. In these preparations, areas of the brainstem and part of the hypothalamus are maintained. Thus, the cardiovascular homeostasis is maintained. In the present study, we performed series of physiological tests for validated the presence of autonomic responses in the model. In addition, we performed a baroreflex study to understand how effective is the model in representing the intact animal. Decerebrated animals were able to keep hemodynamic variables constant during the tail lift protocol. In the head lift maneuver, the systemic mean arterial pressure (MAP sys) increased to ensure adequate blood supply to the head. In addition, during surface heat application, the heart rate (fH) increased, a cardiovascular response typical of Squamata group members during heating. Pharmacological stimulation of O₂ chemoreceptors induced elevations in fH and changes in net shunt. These tests attest that diverse populations of baroreceptors, O₂ chemoreceptors and temperature sensors have functional afferences generating autonomic reflexes even after the decerebration procedure. This indicates that the ANS of the decerebrated animals remains functional and capable of performing hemodynamic compensations to various perturbations. The study of the baroreflex through the pharmacological method indicated that the decerebrated animals maintain the gain and baroreflex limits similar to intact animals. We conclude that the decerebration doesn’t eliminate the reflexes generated by the centers of cardiovascular integration in the central nervous system (CNS) of rattlesnakes, keeping it functional like intact animals. In addition, isoflurane anesthesia suppresses the baroreflex of the decerebrated animals, modify the responses to autonomic function protocols, and causes a decrease of the mean arterial pressure. Thus, the use of anesthesia in the course of experimental protocols involving autonomic reflexes is not indicated.